Robotic versus laparoscopic right hemicolectomy with complete mesocolic excision: a retrospective multicenter study with propensity score matching - Tian, Yue; Xiong, Dehai; Xu, Ming; Fan, Qi; Zheng, Huichao; Shen, Haode; Huang, Bin; Wang, Li; Li, Chunxue; Zhang, Anping; Liu, Baohua; Li, Fan; et al. (Frontiers in Oncology, 2023)
Objective: During the past decade, the concept of complete mesocolic excision (CME) has been developed in attempt to minimize recurrence for right-sided colon cancer. This study aims to compare outcomes of robotic versus laparoscopic right hemicolectomy with CME for right-sided colon cancer. Methods: We performed a retrospective multicenter propensity score matching study. From July 2016 to July 2021, 382 consecutive patients from different Chinese surgical departments were available for inclusion out of an initial cohort of 412, who underwent robotic or laparoscopic right hemicolectomy with CME. Data of all patients were retrospectively collected and reviewed. Of these, 149 cases were performed by a robotic approach, while the other 233 cases were done by laparoscopy. Propensity score matching was applied at a ratio of 1:1 to compare perioperative, pathologic and oncologic outcomes between the robotic and the laparoscopic groups (n = 142). Results: Before propensity score matching, there were no statistical differences regarding the sex, history of abdominal surgery, body mass index (BMI), American Joint Committee on Cancer(AJCC) staging system, tumor lo cation and center between groups(P>0.05), while a significant difference was observed regarding the age(P=0.029). After matching, two comparable groups of 142 cases were obtained with equivalent patient characteristics (P>0.05). Blood loss, time to oral intake, return of bowel function, length of stay and complications were not different between groups (P>0.05). The robotic group showed a significantly lower conversion rate (0% vs. 4.2%, P=0.03), but a longer operative time (200.9 min vs. 182.3 min, P<0.001) and a higher total hospital cost (85016 RMB vs. 58266 RMB, P<0.001) compared with the laparoscopic group. Incidence of complications, mortality and pathologic outcomes were similar between groups (P>0.05). The two-year disease-free survival rates were 84.9% and 87.1% (P = 0.679) and the overall survival rates between groups were 83.8% and 80.7% (P = 0.943). Conclusion: Despite the limitations of a retrospective analysis, the outcomes of robotic right hemicolectomy with CME were comparable to the laparoscopic procedures with fewer conversions to open surgery. More clinical advantages of robotic surgery system need to be further confirmed by well-conducted randomized clinical trials with large cohorts of patients.